2007
DOI: 10.1089/jpm.2006.0200
|View full text |Cite
|
Sign up to set email alerts
|

Illness Awareness of Patients in Hospice: Psychological Evaluation and Perception of Family Members and Medical Staff

Abstract: Despite the fact that patients in hospice were in the terminal phase of disease, 30% of patients had no diagnosis awareness, and an even higher percentage of patients (62%) who had no prognosis awareness.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
48
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 29 publications
(49 citation statements)
references
References 22 publications
1
48
0
Order By: Relevance
“…Some of the patients may not know they have cancer, some of them, knowing the diagnosis, "play along", as if they did not know [19]. So far there is no standardized questionnaire, and using semi-structured clinical interviews is the most common method [20,21]. We interviewed both patients and their accompanying relatives in order to strengthen the accuracy of the findings.…”
Section: Discussionmentioning
confidence: 99%
“…Some of the patients may not know they have cancer, some of them, knowing the diagnosis, "play along", as if they did not know [19]. So far there is no standardized questionnaire, and using semi-structured clinical interviews is the most common method [20,21]. We interviewed both patients and their accompanying relatives in order to strengthen the accuracy of the findings.…”
Section: Discussionmentioning
confidence: 99%
“…To assess the awareness of the prognosis and perception of the goals of therapy, we adapted and modified the following two self-report items, just as was done in previous studies with patients with advanced cancer [14,15]. To assess perceptions of the goals of therapy, we asked the patients the following question: BWhat is the purpose of your treatment?^Patients were categorized into the Baccurate awareness^group if they used terms including Breduce my pain/symptom management or extend my lifetime,^but if they used Bto recover from my cancer/illness^or BI do not know,^the patients were classified into the Binaccurate awareness^category.…”
Section: Methodsmentioning
confidence: 99%
“…However, the prevalence of disease prognosis and perception of treatment purpose were inconsistent in these studies. For instance, the study by Andruccioli et al [14] evaluated the awareness of patients regarding their prognosis, and the findings of this study showed that 62 % of cancer patients were not aware of the progression of their disease. More recently, a study that was conducted in South Korea reported that approximately 90 % of the incurable cancer patients had an unrealistic expectation about their disease progression during chemotherapy [15].…”
Section: Introductionmentioning
confidence: 99%
“…24,25 However, in this study we found that many patients with lifelimiting illness do not discuss their illness in terms of prognosis. [26][27][28] We also found differences among disease groups in discussions of symptoms and causality. Some subjects with COPD and CHF mentioned symptoms and functional limitations associated with their illness.…”
Section: Discussionmentioning
confidence: 65%